Oxygen and clumped isotope fractionation during the formation of Mg calcite via an amorphous precursor - Dietzel, Martin; Kluge, Tobias (Geochimica et cosmochimica acta, 2020)
The oxygen and clumped isotope signatures of Mg calcites are routinely used as environmental proxies in a broad range of surroundings, where Mg calcite forms either by classical nucleation or via an amorphous calcium magnesium carbonate (ACMC) precursor. Although the (trans)formation of ACMC to Mg calcite has been identified for an increasing number of settings, the behavior of both isotope proxies throughout this stage is still unexplored. In the present study ACMC (trans)formation experiments were carried out at constant pH (8.30±0.03) and temperature (25.00±0.03°C) to yield high Mg calcite (up to 20mol%Mg). The experimental data indicate that the oxygen isotope values of the amorphous and/or crystalline precipitate (δ18Oprec, analyzed as Mg calcite) are affected by the (trans)formation pathway, whereas clumped isotopes (Δ47prec=Δ47Mg-calcite) are not. The oxygen isotope evolution of the solid phase can be explained by the instantaneous trapping of the isotopic composition of the aqueous (bi)carbonate complexes. This entrapment results in remarkably high 103ln(αprec-H2O) values of ∼33‰ at the initial ACMC formation stage. During the ACMC transformation process the oxygen isotope equilibrium is approached rapidly between Mg calcite and water (Δ18OMg calcite-water=30.3±0.4‰) and no isotopic memory of the initial to the final Mg calcite at the end of the experiment occurs. The implications for oxygen and clumped isotope signatures of Mg calcite formed via ACMC are discussed in the aspects of various scenarios of (trans)formation conditions and their use as environmental proxies.
Gesehen am 09.07.2020